ESTIMASI NILAI AVERAGE VALUE AT RISK PADA SAHAM PORTOFOLIO DENGAN MENGGUNAKAN METODE ANALISIS KOMPONEN UTAMA - NIKASARI, NI LUH; DHARMAWAN, KOMANG; SRINADI, I GUSTI AYU MADE (E-Jurnal Matematika, 2017)
There are several methods that can be used to measure the risk of a portfolio of stocks. One of them is Average Value at Risk (AVaR). The purpose of this study is to implement Principal Component Analysis (PCA) to select stocks to be incorporated in the portfolio and also to compare the AVaR of the portfolio when  the stocks selected using PCA and selected using mean-variance method. The data we used are the closing price of the stocks BBCA, BDMN, ICBP, INTP, CPIN, KLBF, GGRM, MNCN, SMCB, and SGRO. The selected stocks using PCA are BBCA, CPIN, INTP and, MNCN with AVaR is 1.0971% for 90% confidence level and for 95% confidence level is 1.1432% whereas by using mean variance method, it is found that BDMN, GGRM, ICBP, and SMCB have to be incorporated in the portfolio with AVaR is 1.3314% for 90% confidence level and 1.4263% for 95% confidence level.
Keywords: Principal Component Analysis; Average Value at Risk; Portfolio Markowitz